2020
DOI: 10.3390/su12229709
|View full text |Cite
|
Sign up to set email alerts
|

How (Un)sustainable Environments Are Related to the Diffusion of COVID-19: The Relation between Coronavirus Disease 2019, Air Pollution, Wind Resource and Energy

Abstract: The pandemic caused by novel coronavirus disease 2019 (COVID-19) is generating a high number of cases and deaths, with negative effects on public health and economic systems. One of the current questions in the contemporary environmental and sustainability debate is how high air pollution and reduced use of renewable energy can affect the diffusion of COVID-19. This study endeavors to explain the relation between days of air pollution, wind resources and energy, and the diffusion of COVID-19 to provide insight… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
106
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 123 publications
(110 citation statements)
references
References 48 publications
4
106
0
Order By: Relevance
“…About 74.5% of infected individuals and 81% of total deaths in Italy caused by COVID-19 are in regions with high pollution concentration [40]. The same results were confirmed in the autumn-winter season of 2020-2021 [41]. The governments should pay attention to cities and regions with high pollution levels because it might have a negative effect on public health and environmental policies, new technologies to reduce the levels of air pollution should be explored [3,42].…”
Section: Introductionmentioning
confidence: 66%
See 2 more Smart Citations
“…About 74.5% of infected individuals and 81% of total deaths in Italy caused by COVID-19 are in regions with high pollution concentration [40]. The same results were confirmed in the autumn-winter season of 2020-2021 [41]. The governments should pay attention to cities and regions with high pollution levels because it might have a negative effect on public health and environmental policies, new technologies to reduce the levels of air pollution should be explored [3,42].…”
Section: Introductionmentioning
confidence: 66%
“…For instance, the highest concentration of confirmed COVID-19 cases was in Northern Italy, the Po valley to be exact, where the five Italian cities with the highest pollution levels are found [65][66][67]. Although some studies have found spatial coincidence among air pollution and high incidence and mortality [38][39][40][41]50,[65][66][67][68], there is a larger uncertainty and further epidemiological research is needed. Figure 3 shows the concentration of NO 2 , PM 2.5 , and PM 10 changes in Europe in the two different periods: 6 January 2020 data before the outbreak of COVID-19 and 31 March 2020, when most of Europe introduced national lockdowns.…”
Section: Air Pollution Analysis In the Context Of Production Reductionmentioning
confidence: 98%
See 1 more Smart Citation
“…This study shows that environment plays a vital role for impact of COVID-19 in society; in particular, a low rate of fatality is associated with a low impact of air pollution on population: considering PM 2.5 air pollution, population exposed to levels exceeding WHO guideline value (% of total) is 72% in countries with a lower fatality rate, whereas in countries with a higher incidence of mortality of COVID-19 is almost 98%! Coccia ( , 2020aCoccia ( , 2020bCoccia ( , 2020c nds out that number of infected people was higher in Italian cities with >100 days per year exceeding limits set for PM 10 or ozone, cities located in hinterland zones (i.e. away from the coast), cities having a low average wind speed and cities with a lower temperature.…”
Section: Environmental Policymentioning
confidence: 98%
“…Source: World Bank (2020d). Studies reveal that areas with frequently high levels of air pollution -exceeding safe levels of ozone or particulate matter -had higher numbers of COVID-19 related infected individuals and deaths (Coccia, , 2020a(Coccia, , 2020b(Coccia, , 2020c(Coccia, , 2020dCoccia, 2021;Martelletti and Martelletti, 2020). Moreover, high concentrations of nitrogen dioxide and particulate air pollutant induce serious damages to the immune system of people, weakening it to cope with infectious diseases of viral agents (Glencross et al, 2020) Containment measure of COVID-19 lockdown is measured with total days of lockdown across countries over 2020-2021 period (until January 2021).…”
Section: Research Setting and Measuresmentioning
confidence: 99%